Hubungan Antara Kecerdasan Emosi dengan Perilaku Prososial Mahasiswa Fakultas Psikologi Universitas Muhammadiyah Surakarta - Hendrianto, Basori, Dr. Nisa Rachmah N A, M.Si (2016)
Emotional intelligence is the ability to motivate and ability to manage emotions themselves and in relationship with others. Prosocial behavior for people with high emotional intelligence will be able to realize and understand the entire process that goes on inside, feelings and behavior. The purpose of this research was to examine the relations between emotional intelligent with pro-social behavior at the student of the faculty of psychology UMS. The subjects of the study were 110 students, consist of 30 male students force 2013, 25 female students force 2013, 30 male students force 2014, and 25 female students force 2014 which is still active college in faculty of psychology university of muhammadiyah surakarta. This research sampling technique using simple random sampling, ie sampling technique sampling of populiasi randomly based on the frequency of the probability of all members of the population. The result of correlation analyses between either emotional intelligence with prosocial behavior showed a positive correlation signifycantly. Variables of emotional intelligent give effective contribution toward prosocial behavior about 64,6 %.